2019
DOI: 10.1371/journal.pone.0218227
|View full text |Cite
|
Sign up to set email alerts
|

The role of alien species on plant-floral visitor network structure in invaded communities

Abstract: The interactions between pairs of native and alien plants via shared use of pollinators have been widely studied. Community level studies however, are necessary in order to fully understand the factors and mechanisms that facilitate successful plant invasion, but these are still scarce. Specifically, few community level studies have considered how differences in invasion level (alien flower abundance), and degree of floral trait similarity between native and invasive species, mediate effects on native plant-po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(64 citation statements)
references
References 60 publications
(151 reference statements)
2
59
1
2
Order By: Relevance
“…), we do not expect environmental constraints to strongly influence plant species overlap in flowering time within a season. Pollinator community at the study area is composed by multiple functional groups but is strongly dominated by bee flies, butterflies, flies, social and solitary bees (Albor et al., 2019; Campos‐Navarrete et al., 2013; Parra‐Tabla et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…), we do not expect environmental constraints to strongly influence plant species overlap in flowering time within a season. Pollinator community at the study area is composed by multiple functional groups but is strongly dominated by bee flies, butterflies, flies, social and solitary bees (Albor et al., 2019; Campos‐Navarrete et al., 2013; Parra‐Tabla et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Although this type of densitydependent relationship has been shown for pairs of interacting plant species (Brown, Mitchell, & Graham, 2002;Jakobsson, Lázaro, & Totland, 2009;Rathcke, 1983Rathcke, , 1988Seifan, Hoch, Hanoteaux, & Tielbörger, 2014), knowledge of density-dependent effects in structuring species interactions at the community level is limited (but see Bergamo, Streher, Traveset, Wolowski, & Sazima, 2020). As a result, along the entire study area, the density and diversity of co-flowering species can be up to 10 and 2 times higher in the rainy season compared to the dry season, respectively (Albor et al, 2019;Parra-Tabla et al, 2019). This seasonal dynamic occurs as a result of drastic changes in the environment (temperature, precipitation) that occur predictably during certain months of the year.…”
Section: Introductionmentioning
confidence: 98%
“…Alien species represent around 30% of total plant richness (Parra‐Tab la et al., 2018) and a high percentage of all the flowers available to pollinators in these communities (76% ± 30, M ± SD ), but with high variability among sites (12%–99%; Table 1). Alien plant species also share a high proportion of the primary insect pollinators with native plant species (Albor et al., 2019; Suárez‐Mariño et al, 2019; Parra‐Tab la et al., 2019). Following Parra‐Tab la et al.…”
Section: Methodsmentioning
confidence: 99%
“…The study of plant–pollinator networks based on flower visitation has further suggested that co‐flowering communities are robust to species invasion (e.g. Parra‐Tab la et al., 2019; Vilà et al., 2009 but see Albrecht et al., 2014). However, if the arrival of alien plant species exacerbates HP transfer, it could affect the robustness of co‐flowering communities and their long‐term stability independently of changes in pollinator visitation (see Fang & Huang, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation